Must Democratic Ecology be Anthropocentric? Reflections on Luc Ferry’s Concepts - Ciążela, Helena (Problemy Ekorozwoju, 2009)
This essay presents critical analysis of Luc Ferry’s concepts on ecology as the author who offered a critique of deep ecology, named by himself as “ecofascism”. However, it must be stressed that his philosophy has a wider reflection as a liberal answer to intellectual problems and dilemmas of the contemporary world. He attempted to systemize philosophical and political fields of ecology around two oppositions: anthropocentrism and cosmocentrism as well as democracy and totalitarism. However, mandatory character of relations proposed by him is problematic. His anthropocentrism seems to be dogmatic, and ecological sensitiveness limits itself to “care for himself”. Restricted range of Ferry’s reflection indicates the way not to ecological democracy, but how to marginalize it. A contemporary human being does not face a choice between anthropocentrism and cosmocentrism, but he must consider to deeper his relations with a complicated system of nature.